(untitled) (Research, Society and Development, 2021)
Students with Down’s Syndrome are part of the target audience of Special Education, with the right to regular school and specialized care. More than staying in school, these students are guaranteed to learn and stay in school, which indicates an advance in legislation in this regard. For inclusion to actually occur, it is necessary that the school adapts to the needs of these subjects, and not the other way around. Learning mathematics is as important as learning to read and write to ensure inclusion. A single case study was carried out with a student with Down syndrome attending the third grade of elementary school at a private school. This article aims to analyze the results of work among peers for the mathematical learning of a child with Down syndrome, using the game Win 100 first, adapted from the Theory of Planned Formation of Mental Actions and Concepts.